Analisis Pengaruh Biaya Premi Asuransi Jiwa Syariah Dan Beban Klaim Terhadap Laba Perusahaan Pada PT. Asuransi Takaful Keluarga - Alwi, Fachri; Yusrizal, Yusrizal; Atika, Atika (Universitas Labuhanbatu, 2022)
This study aims to find out how much influence the cost of ipremiasuransi ijiwa isyariah idan Iban iklaim iterhadap ilaba iperusahaan iperusahaan iTakaful iKeluarga. the type of research I used was quantitative descriptive research, the technique of collecting data on this research I was using the documentation technique I took from iweb i family insurance company, and the sample I used i16 monthly financial report. The data testing techniques used in this study include sumyclassical testing, multiple ilinear regression testing and hypothesis testing using the iSPSS program.The results of this study show that the iparsial ipremi costs affect positively and significantly against the company's iLaba I0.048 I<0.05 I and the burden of claim I do not affect positively and do not significantly affect the company's Laba I0. 482 I> i0. 05. isimultan isimultan iBiayaPremi idan iburban I claim iberpengaraan ibersama ITER iterhadap iLaba iperusahaand dengan ini isignifikansi i0,002 I< i0, 05. iDan iUji iR iSquare ipremi Idi costsidanburban iKlaim imempengarau iLaba iperusahaan isebesar i62% ipada iPT. family insurance.